Erdheim-Chester Disease - Melissa Matzumura MD (Journal of Investigative Medicine High Impact Case Reports, 2016)
Erdheim-Chester disease (ECD) is a rare, xanthogranulomatous, non-Langerhans cell histiocytosis with frequent systemic involvement. Although the diagnosis is based on characteristic histological and radiological findings, its identification can be challenging because of its heterogeneous presentation. Osteosclerosis of long bones, often associated with bone pain, is the most common initial manifestation, followed by extraskeletal manifestations in approximately 50% of cases. There is no standard treatment for ECD, although recommendations have been made on the basis of small studies. A systematic approach to the diagnosis of ECD is important, because its manifestations may be life-threatening and may require specific management. We report an atypical presentation of ECD, with early cardiac, renal, and central nervous system involvement, and only late skeletal manifestations.